Performance Evaluation and Forecasting Functions and the Perceived Value of the Budget - Mucci, Daniel Magalhães; Beck, Franciele; Frezatti, Fábio (Advances in Scientific and Applied Accounting, 2023)
Objective: To investigate the association between performance evaluation and forecasting functions and the value perceived by managers concerning the budget, considering jointly the logics of trade-off and the predominance among the budgetary functions. Methodology: A survey was conducted with a sample of 109 medium and large-sized companies that use budgeting. The data were analyzed using Structural Equation Modeling. Results: First, the results indicate that the simultaneous use of the budget for performance evaluation and forecasting functions leads to a decrease in the value perceived by managers concerning the budget, signaling the presence of a potential trade-off between these functions. Second, this study also investigated to what extent the predominance of the budget for one of the two functions would mitigate the observed trade-off, but the results were not significant. Contributions: This research provides evidence contributing to the discussion of the trade-off between performance evaluation and forecasting functions but does not support that the predominance of one function over the other reduces this tension. This outcome adds to the evidence from previous studies. From a practical standpoint, the study shows that these functions, individually, might encourage managers to recognize the importance of the budget, yet it demonstrates a potential trade-off between these functions, with a higher perceived value associated with the performance evaluation function.